Excess Pyrophosphate Restrains Pavement Cell Morphogenesis and Alters Organ Flatness in Arabidopsis thaliana - Gunji, Shizuka; Oda, Yoshihisa; Takigawa-Imamura, Hisako; Tsukaya, Hirokazu; Ferjani, Ali (Frontiers in Plant Science, 2020)
In Arabidopsis thaliana, the vacuolar proton-pumping pyrophosphatase (H+-PPase) is highly expressed in young tissues, which consume large amounts of energy in the form of nucleoside triphosphates and produce pyrophosphate (PPi) as a byproduct. We reported that excess PPi in the H+-PPase loss-of-function fugu5 mutant severely compromised gluconeogenesis from seed storage lipids, arrested cell division in cotyledonary palisade tissue, and triggered compensated cell enlargement; this phenotype was recovered upon sucrose supply. Thus, we provided evidence that the hydrolysis of inhibitory PPi, rather than vacuolar acidification, is the major contribution of H+-PPase during seedling establishment. Here, examination of the epidermis revealed that fugu5 pavement cells exhibited defective puzzle-cell formation. Importantly, removal of PPi from fugu5 background by the yeast cytosolic PPase IPP1, in fugu5-1 AVP1pro:IPP1 transgenic lines, restored the phenotypic aberrations of fugu5 pavement cells. Surprisingly, pavement cells in mutants with defects in gluconeogenesis (pck1-2) or the glyoxylate cycle (icl-2; mls-2) showed no phenotypic alteration, indicating that reduced sucrose production from seed storage lipids is not the cause of fugu5 epidermal phenotype. fugu5 had oblong cotyledons similar to those of angustifolia-1 (an-1), whose leaf pavement cells display an abnormal arrangement of cortical microtubules (MTs). To gain insight into the genetic interaction between ANGUSTIFOLIA and H+-PPase in pavement cell differentiation, an-1 fugu5-1 was analyzed. Surprisingly, epidermis developmental defects were synergistically enhanced in the double mutant. In fact, an-1 fugu5-1 pavement cells showed a striking three-dimensional growth phenotype on both abaxial and adaxial sides of cotyledons, which was recovered by hydrolysis of PPi in an-1 fugu5-1 AVP1pro:IPP1. Live imaging revealed that cortical MTs exhibited a reduced velocity, were slightly fragmented and sparse in the above lines compared to the WT. Consistently, addition of PPi in vitro led to a dose-dependent delay of tubulin polymerization, thus supporting a link between PPi and MT dynamics. Moreover, mathematical simulation of three-dimensional growth based on cotyledon proximo-distal and medio-lateral phenotypic quantification implicated restricted cotyledon expansion along the medio-lateral axis in the crinkled surface of an-1 fugu5-1. Together, our data suggest that PPi homeostasis is a prerequisite for proper pavement cell morphogenesis, epidermal growth and development, and organ flattening.